Pola Komunikasi Penjual Terhadap Pembeli Pempek di Kota Palembang (Jurnal Ilmu Komunikasi dan Bisnis, 2020)
The Pattern of Communication is an important thing to support our daily communication process. Communication pattern is formed due to repeated habits that occur continuously in different situations and conditions that are found in everyday life. This study will focus on the patterns of communication used between Pempek sellers and consumers, as well as in Pempek Beringin Restaurant Gudang Makan-Kenten Street, Jln. MP. Mangkunegara, Palembang in South Sumatera. Methodology used is a qualitative methodology with ethnography. The theory used is the theory of symbolic interaction. Data collected by in-depth interviews and field observations with three informants: two of CV. Pesona Musi’s employee and one of the consumer. The results from in-depth interviews and author’s observations in the field are the following that the communication patterns between sellers with consumers in Pempek Beringin Restaurant are going well until now.